Kearifan Lokal Larung Sesaji Di Danau Ngebel Ponorogo - Muhaimin, M Zunaidul (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to examine Larung Sesaji as a pillar of love (mahabbah), tolerance (tasamuh), and Islamic values that can be integrated into efforts to build global harmony. The Larung Sesaji tradition at Lake Ngebel Ponorogo is a form of local wisdom that is rich in philosophical and spiritual meaning. This tradition reflects the values of togetherness, respect for nature, and appreciation for social diversity that coexists in Ponorogo society. Using a qualitative approach through observation, interviews, and literature study, this study reveals that Larung Sesaji contains a universal message about the harmony of human relationships with God, fellow human beings, and the environment. These values are in line with Islamic teachings that emphasize compassion, peace, and tolerance. The results of the study show that this local wisdom can be a model for dialogue between cultures and religions, as well as a real contribution to building a global civilization.